Integrated Corporate Social Innovation for Urban Coastal Resilience: Evidence from the Lawang Cemoro Program in Indonesia - Aryo Aji Asmoro; Antika Sukma Pandanarum; Mirtha Aulia Putri (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Coastal areas face a variety of complex challenges, including environmental pollution, limited access to clean water, poor public health, and social and economic vulnerability. These conditions call for a development approach that is not only environmentally focused but also capable of strengthening community capacity in a sustainable manner. This study aims to analyze the implementation of the LAWANG CEMORO Program (Gateway of Hope for the People of North Semarang) as a social innovation by PT Pertamina Patra Niaga Integrated Terminal Semarang in building coastal resilience through a sustainable development approach. The study employs a qualitative method using a case study approach. Data were collected through observation, interviews, documentation, and literature review, and were then analyzed descriptively using a sustainable development framework. The research findings show that the LAWANG CEMORO Program is implemented through four main pillars: Manfaati Sampah, Tirto Migunani, Sehat Jiwa Raga, and Pasinaon. The “Manfaati Sampah” pillar successfully promotes the circular economy through the management of economically valuable waste; “Tirto Migunani” enhances water resilience through the use of solar-powered, environmentally friendly water filtration technology (SITIRTA); “Sehat Jiwa Raga” strengthens social resilience through preventive health services and protection for vulnerable groups; and “Pasinaon” builds community capacity through education, training, and economic empowerment. The implementation of these four pillars has had a positive impact on improving the quality of the environment, health, social capacity, and the economic self-reliance of coastal communities. Research findings indicate that collaboration between companies, the government, and the community through social innovations based on local needs can strengthen the resilience of coastal areas while supporting the achievement of the Sustainable Development Goals (SDGs).